Mid infrared gas spectroscopy using efficient fiber laser driven photonic chip-based supercontinuum - Davide Grassani (Nature Portfolio, 2019)
The mid-infrared spectral region is important for gas sensing applications. Here, Grassani et al. demonstrate efficient supercontinuum generation from fibre-lasers injected into silicon nitride waveguides to provide a turn-key mid-IR source with milliwatt-level output.